Nka Roundtable II - (:unkn) unknown (My University, 2010)
Participants: Okwui Enwezor, Elizabeth Harney, dele jegede, Sidney Kasfir, Dominique Malaquais, Steven Nelson, Chika Okeke-Agulu, Ikem Stanley Okoye, John Peffer, John Picton, Peter Probst, Colin Richards, Frank Ugiomoh, Susan Vogel et Jessica Winegar
Keywords: African Research